Analisis Faktor Risiko Ergonomi Pada Pekerja Pembuat Jaja Sengait Di Desa Sading Mengwi Badung - Ni Luh Putu Mia Lestari Devi; Ni Putu Sri Arnita; Maqfirah Muryanifa (Asosiasi Riset Ilmu Kesehatan Indonesia, 2023)
The home industry that is developing in Sading village is the sengait jaja industry. This is due to the large number of requests and relatively cheap prices. Ergonomics analysis is needed to create safe, comfortable, healthy working conditions, so as to create effective work activities and can increase productivity. The method used in this research is descriptive with observation, interview, and documentation methods. The results of this study were analyzed descriptively with an ergonomic approach. The results of this study are the occurrence of repetitive movements, bad working posture, static working positions, extreme temperatures and work stress in workers who make jaja sengait. From the results of this analysis it can be suggested by (a) redesigning the work station; (b) adapting work facilities to anthropometry and types of work, so that work attitudes can be more ergonomic; (c) work environment and carrying out exercise actions in between breaks to reduce musculoskeletal disorders, fatigue and can reduce boredom at work so that productivity increases.